Characteristics Of Non-Hemorrhagic Stroke Patients In The Medical Rehabilitation Clinic Of Datu Sanggul Regional Hospital in 2024 : A Retrospective Study - Siti Rasyidah; Misda Haryatni (International Journal of Health Engineering and Technology, 2026)
Stroke is a leading cause of disability and the second leading cause of death worldwide. Medical rehabilitation plays a vital role in post-stroke recovery In Indonesia, the prevalence of stroke shows a continuing increasing case. Data from the 2018 Basic Health Research (Riskesdas) recorded a stroke prevalence of 10.9 per 1,000 population. To describe the characteristics of stroke patients undergoing medical rehabilitation at Datu Sanggul Regional Hospital. This study used a retrospective descriptive design with a cross-sectional approach. Secondary data were obtained from electronic medical records of stroke patients who underwent medical rehabilitation in 2024. A total of 80 patients with non-hemorrhagic stroke were included. The largest age group was 50–59 years (35%). Male patients predominated compared to females (53.75% vs 46.25%). The most common comorbidity was hypertension (65%), followed by diabetes mellitus (35%), dyslipidemia (31.25%), heart disease (25%), obesity (12.5%), chronic kidney disease (10%), and previous stroke (15%). Most patients had more than one comorbidity. The therapeutic modalities were predominantly centered on core interventions, including NMES and exercise (100%), IRR(93,7%), IF (90%) and other adjuvant therapies. Non-hemorrhagic stroke patients at Datu Sanggul Regional Hospital were predominantly in the late productive age group and had significant vascular risk factors. These findings highlight the urgent need for comprehensive medical rehabilitation services and the presence of physical medicine and rehabilitation specialists can significantly accelerate the functional recovery process in stroke patients.